C-type natriuretic peptide stimulates osteoblastic proliferation and collagen-X expression but suppresses fibroblast growth factor-23 expression in vitro - Wei Xia Chen; Hui Hui Liu; Rui Xue Li; Goshgar Mammadov; Jing Jing Wang; Fei Fei Liu; Sama Samadli; Yang Fang Wu; Dong Dong Zhang; Huang Huang Luo; Peng Hu (BMC, 2020)
Abstract Background The effects of C-type natriuretic peptide (CNP) and fibroblast growth factor (FGF)-23 appear to oppose each other during the process of bone formation, whereas few studies exist on the interaction between CNP and FGF-23. The main objective of the present study is to probe whether CNP is directly responsible for the regulation of osteoblast or via antagonizing FGF-23. Methods Osteoblasts were cultured in the absence or presence of CNP (0, 10, and 100 pmol/L) for 24 h, 48 h and 72 h, respectively. Results The findings of the present study indicated that: (1) CNP significantly stimulated osteoblastic proliferation and collagen (Col)-X expression; (2) both osteoblastic (osteocalcin, procollagen type I carboxy-terminal propeptide, total alkaline phosphatase and bone-specific alkaline phosphatase) and osteolytic (tartrate-resistant acid phosphatase and cross-linked carboxyterminal telopeptide of type I collagen) bone turnover biomarkers were up-regulated by CNP in osteoblasts; (3) FGF-23 mRNA and protein were significantly down-regulated at 24 h by CNP in osteoblasts, but the expression of FGF receptor-1/Klotho had no significant change. Conclusions CNP stimulates osteoblastic proliferation and Col-X expression via the down-regulation of FGF-23 possibly in vitro. However, the specific mechanisms of the interaction between CNP and FGF-23 in osteoblasts are still unclear according to our findings. A further study on osteoblasts cultured with CNP and FGF-23 inhibitor will be undertaken in our laboratory.